The Model of Sense of Belonging and Work Effectiveness - Elvie Maria; Peni Cahyati; Nurdiana Mulyatini; Tetet Kartilah; April Gunawan Malau (Dinasti Publisher, 2024)
This study aims to develop a theoretical model that explores the relationship between sense of belonging and work effectiveness among employees. Sense of belonging, defined as an individual’s feeling of being a valued and integral part of an organization, has been increasingly recognized as a crucial factor in enhancing employee motivation and performance. However, the mechanisms through which sense of belonging influences work effectiveness remain underexplored. Through a comprehensive literature review and empirical analysis, this paper proposes a model that illustrates how sense of belonging impacts work effectiveness directly and indirectly through mediating variables such as job satisfaction, organizational commitment, and employee engagement. Data were collected from a diverse sample of employees across various industries, and the results indicate a significant positive correlation between sense of belonging and work effectiveness. The findings suggest that fostering a strong sense of belonging within organizations can lead to improved work outcomes, providing valuable insights for human resource management practices